Mémoires sensibles de l’eau. Apprentis marins sur l’île du Frioul dans les années 1950 - Dominique Maillard (Images du Travail, Travail des Images)
This article contributes to the writing of a sensitive history of training and education at sea, from the study of a Maritime Learning School in Marseilles, set up in the 1950s, off the city of Marseilles, on one of the islands of Frioul. By using a memory source produced by alumni and made on one hand by pictures and on the other hand by discourses about their stay with the school, the analysis focuses on how the particular space-time conditions of this teaching played for these boys and young men as a propaedeutic of the sea. Whereas in the island of Frioul there’s no physical evidence of the school and more than 60 years after the last pupils left it, how to capture a collective memory of the school from the materiality of the place, the images and the discourses?